Feminisme dan Politik: Mengurai Hambatan dan Peluang Bagi Pemimpin Perempuan - Chandra Dimuka Suharno; Febriani Nurul Awaliah; Farah Salma Rubbiyanti; Fawwaz As’ad Rizqullah (Transgenera: Jurnal Sosial, Politik dan Humaniora, 2025)
The goal of the social, political, and intellectual movement known as feminism is to eliminate gender-based inequalities. Participation that forms gender stereotypes about women's issues and politics in general includes women's political rights. Research Methods This article To investigate the potential and challenges faced by women political leaders from a feminist perspective, this study uses qualitative techniques with a case study design. stereotype is when a person or group of people are given certain characteristics based on subjective classifications simply because they belong to a particular group (in-group or out-group), which can be positive or negative. The dual role of women in Indonesian politics is complicated, they often have to balance their responsibilities as housewives with their political roles as activists or leaders. The theoretical analysis that has been given states that the theory of violation of expectations describes a situation where an individual has expectations or hopes for the nonverbal behavior of others. Stereotypes are perceptions or beliefs about groups or people that are based on pre-existing opinions and attitudes.